STRONG TEST PRESSURE CONCRETE USE OF ASBEST WASTE - Saiful Muslimin; Suwarno Suwarno; April Gunarto; M Zaenuri (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
Concrete is a significant and most dominant material used in building structures. Concrete consists of a mixture of cement, aggregate, water, and added ingredients. Concrete said material has an essential role in making concrete because it can change the real properties to suit the needs. Li, asbestos is a concrete-added material that can reduce the use of cement and produce concrete with absolute consistency. The purpose of this study was to determine how the effect of adding asbestos waste to cement. The method used is an experimental method based on previous research. The specimen used was cylindrical with a diameter of 15 cm and a height of 30 cm. The percentage variation of asbestos waste addition is 0%, 50%, and 100% of the weight of cement used. Typical concrete test results obtained an average value of 22.08 MPa, a 50% percentage produces an average compressive strength of 21.32 MPa, and a portion of 100% provides a compressive strength of 22.93 MPa. Then the results of the then actual strength test have increased in the percentage of asbestos waste 100%.